Geometridae (Lepidoptera) e Hymenoptera parasitoides em área de Mata Estacional Semidecídua na Estação Ecológica de Jataí, Luiz Antônio - SP - Geraldo, Mariana (2017)
Larvae of Geometridae (Lepidoptera) were obtained with an entomological umbrella, from October 2013 to September 2015, in two areas of semi-deciduous forest (Mata/Cerradão and Mata) at Estação Ecológica de Jataí, Luiz Antônio, São Paulo state. The larvae of Geometridae were kept in the laboratory until the adult or parasitoid emergence. Especimens of the families Braconidae and Ichneumonidae were obtained, from January 2014 to February 2015, with two Malaise traps located in the same local of collection of Geometridae larvae. The material obtained in the Malaise traps was sorted, the individuals of the families Braconidae and Ichneumonidae were identified in subfamily level and the Microgastrinae, Cheloninae and Rogadinae, Campopleginae and Mesochorinae subfamilies were identified at the genus level. A total of 416 larvae of Geometridae weas collected, 190 in the Mata/Cerradão stretch and 226 in the Mata stretch, of which, 52 and 39, respectively, were parasitized. Among the Geometridae, the subfamily Ennominae was represented by individuals of 14 genera (Argyrotome, Glena, Hymenomima, Iridopsis, Ischnopteris, Lomographa, Macaria, Nepheloleuca, Patalene, Phrygionis, Physocleora, Prochoerodes, Rhomboptila and Trotopera), the subfamily Larentiinae by four (Eubaphe, Eupithecia, Euphyia and Pterocypha) and the subfamily Sterrhinae by two (Cyclophora and Idaea). A total of 91 larvae of Geometridae, from 11 genera, were obtained parasitized by 198 parasitoids. The parasitoids obtained belong to the families Braconidae, Ichneumonidae, Eulophidae and Diptera. The Malaise traps provided 2720 individuals of the Ichneumonoidea superfamily, of these 1210 are Braconidae and 1510 are Ichneumonidae, in the Mata/Cerradão stretch, and 702 in the Mata stretch, of which 214 individuals of the Braconidae family and 488 individuals of the Ichneumonidae family. Among the Braconidae, the subfamily Microgastrinae was the most abundant, with 44.5% of individuals in the Mata/Cerradão stretch and 31.8% in the Mata stretch. Eighteen genera of Microgastrinae were recorded (Alphomelon, Apanteles, Choeras, Cotesia, Diolcogaster, Distatrix, Glyptapanteles, Hypomicrogaster, Iconella, Microplitis, Papanteles, Parapanteles, Pholetesor, Prasmodon, Promicrogaster, Protapanteles, Pseudapanteles and Rasivalva), five of Rogadinae (Aleiodes, Choreborogas, Rogas, Stiropius and Yelicones) and four of Cheloninae (Ascogaster, Chelonus, Microchelonus and Phanerotoma). Between the Ichneumonidae collected, 161 individuals were obtained from the subfamily Campopleginae in the Mata/Cerradão stretch and 35 in the Mata stretch. The genera of Campopleginae obtained were Campoletis, Campoplex, Casinaria, Charops, Cryptophion, Cymodusa, Diadegma, Dusona, Hyposoter, Microcharops and Venturia.